The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2006
DOI: 10.1021/ol062736s
|View full text |Cite
|
Sign up to set email alerts
|

α,α‘-Annulation of 2,6-Prenyl-Substituted Cyclohexanone Derivatives with Malonyl Chloride:  Application to a Short Synthesis of (±)-Clusianone. Formation and Rearrangement of a Biogenetic-Like Intermediate

Abstract: Conditions were found for the successful Effenberger alpha,alpha'-annulation of 3,3-dimethyl-2,4,6-triprenyl cyclohexanone silyl enol ethers with malonyl chloride to give the corresponding bicyclo[3.3.1]nonane-trione in 35% yield, this result allowing a short synthesis of (+/-)-clusianone. An isomeric rearranged bicyclo[3.3.1]nonane-trione was also isolated in 25% yield, and changing the Lewis acid resulted in formation of a lavandulyl-substituted phloroglucinol derivative in 38% yield. The mechanism of format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
41
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(44 citation statements)
references
References 11 publications
0
41
0
2
Order By: Relevance
“…9 Syntheses of clusianone (type B) were subsequently reported by several groups 10 including ours. 11 Nemorosone also has been the subject of a total synthesis. 10e Our interest in the field of PPAPs came from the observation that xanthochymol was active in a tubulin disassembly inhibition test.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…9 Syntheses of clusianone (type B) were subsequently reported by several groups 10 including ours. 11 Nemorosone also has been the subject of a total synthesis. 10e Our interest in the field of PPAPs came from the observation that xanthochymol was active in a tubulin disassembly inhibition test.…”
Section: Introductionmentioning
confidence: 99%
“…6 After our work leading to the isolation of oblongifolins A-D, 12 we undertook synthetic studies toward type B PPAPs. 11,13 We previously showed that the boron trifluoride catalyzed Effenberger α,α'-annulation 14 of isomeric 2,4,6-triprenyl-3,3-dimethylcyclohexanones TMS enol ethers 1 with malonyl dichloride allowed the formation of the bicyclo[3.3.1]nonane-2,4,9-trione 2 with an equatorial prenyl group. 11 This led to a short synthesis of (±)-clusianone via C-benzoylation of the enolic β-dicarbonyl moiety of 2 (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…1). In addition, further characterizations of 1-4 were conducted utilizing 1 HNMR and 13 CNMR spectroscopy to characterize both tautomers (a/b) present. Data on clusianone and analogues are available as Supporting Information.…”
mentioning
confidence: 99%